OCCUPATIONAL HEALTH AND SAFETY PRACTICES IN THE WORKPLACE DURING THE COVID-19 PANDEMIC: A LITERATURE REVIEW - Islamiyah Syamila, Ana; Indrayani, Reny; Ismi Hartanti, Ragil; Dewi Prahastuti Sujoso, Anita (Journal of Vocational Health Studies, 2024)
Background: The Corona Virus Disease 2019 (COVID-19) pandemic, which has impacted the world of work, has necessitated work organizations to prevent transmission and enhance workers’ performance. Purpose: To find out the implementation of occupational health and safety management during the COVID-19 pandemic across various corporate sectors. Review: It was conducted by answering research questions related to the management of safety and health practices in the workplace during the COVID-19 pandemic. The process involved formulating problem questions based on the PICOS framework. After filtering and adjusting the research variables, 21 articles were analyzed, consisting 12 articles from the ProQuest database and 9 articles from the ScienceDirect database. Result: Various innovations have been made by companies so that the implementation of Occupational Health and Safety (OHS) management, especially health protocols in dealing with COVID-19, can run optimally. Among them is an increasing number of training sessions for workers on health protocols and awareness, redesigning workplaces according to standards, using smart technology to detect social distancing violations, and improving dialogic communication. Such improvements have been proven to increase communal relations between workers and management, thereby increasing active worker participation in establishing a safe working culture within the workplace. Conclusion: The OHS management implemented by the company may change based on workplace COVID-19 prevention regulations.